Drinking water quality and associated factors in Bahir Dar City and the surrounding rural areas, Northwest Ethiopia: a community-based cross-sectional study - Baye Sitotaw; Derebew Teferi; Zinash Wossen; Beselam Tadesse (Journal of Water, Sanitation and Hygiene for Development, 2023)
In low-income countries like Ethiopia, waterborne illnesses have posed serious public health problems. This study aimed to evaluate drinking water quality (DWQ) and associated factors in Bahir Dar City and the surrounding rural areas in northwest Ethiopia. A cross-sectional study was conducted from January to June 2022 to determine coliform counts and basic physicochemical parameters from the drinking water samples (DWS) collected from urban, peri-urban, and rural sites. A total of 180 DWS were collected from water collection points and households' containers. Potentially pathogenic bacteria were also isolated from fecal coliform (FC)-positive samples and their antibiotic susceptibility profiles were determined. Moreover, the risk factors associated with water quality were assessed. The water quality test results were evaluated against the WHO guidelines for DWQ. Based on the results of this study, only 16.7 and 73.88% of samples met the standards for total coliform and FC, respectively. Moreover, 95.4 and 43% of the isolated bacteria were resistant at least to one of the commonly used antibiotics and multidrug-resistant, respectively. Educating the public on proper drinking water handling, appropriate treatment, and waterline maintenance are needed to safeguard the community from waterborne diseases. HIGHLIGHTS Most of the drinking water in Bahir Dar City does not comply with the WHO standards.; There were poor drinking water disinfection practices in Bahir Dar City.; Drinking water quality in rural areas of Bahir Dar City was at a high sanitary standard.; There were poor drinking water handling practices in Bahir Dar City at the household levels.; Access to low-drinking water was prevalent in Bahir Dar City.;